1989
DOI: 10.1002/j.0022-0337.1989.53.12.tb02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of stress among third‐year dental students

Abstract: The purpose of this study was to identify the perceived stress of third‐year dental students using a large sample (four classes). The dental environmental stress (DES) questionnaire was administered to 263 (87.7 percent) third‐year students from 1984 to 1988. The top six stress items, as perceived by third‐year students, included examinations and grades, graduation requirements, inconsistency of professor's feedback, patient tardiness or no show, atmosphere created by clinical faculty, and financial responsibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 0 publications
3
46
1
2
Order By: Relevance
“…As stated in the Introduction, studies have shown that stress among medical students falls off the further into their education they progress [4], whereas the stress level of dental students rises sharply at their third year, i.e. the first clinical year [4] [8]. This may have been an alternative explanation for our results, since third year dental students perceived higher levels of stress than did fourth year medical students.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As stated in the Introduction, studies have shown that stress among medical students falls off the further into their education they progress [4], whereas the stress level of dental students rises sharply at their third year, i.e. the first clinical year [4] [8]. This may have been an alternative explanation for our results, since third year dental students perceived higher levels of stress than did fourth year medical students.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have shown that dental students [1] [2] [3] [4] and medical students [4] [5] [6] often experience negative stress symptoms during their education, especially in the years of transition from preclinical to clinical competencies [4] [7] [8] [9] [10]. Studies also show that stress intensity levels fall the further medical students progress in their education [4], while dental students' stress levels meaningfully increase in their first clinical year, which is usually the third year [4] [8]. Stress levels were determined with the same measures in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…academic performance, faculty relations, patient and clinic responsibilities, personal life issues and professional identity. A modified version of the Dental Environmental Stress questionnaire compiled by Westerman et al [17][18] was used as the original template for the survey. The overall findings of the investigation showed that dental students perceived that they experienced greater levels of stress than medical students in three of the five measured categories.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2. Generally speaking, evaluations can provoke intense stress levels in students and require a high level of responsiveness, 22,[40][41][42][43] given that they must pass said exams to complete the terms and program.…”
mentioning
confidence: 99%
“…Yet we can affirm that the academic factor is the most relevant stressor, as reflected in other studies. 22,35,40,41,47,48 That being said, this factor is not exclusive, as it interacts with others. If a student fails his or her exams, he or she will not pass their courses, will have to face their parents and professors after a failing grade, and may have subsequent personal problems (daily life factor), as described by Yap et al 40 Furthermore, the atmosphere in the clinic item is essential to distinguishing the first period from the second, and reflects the transition from basic sciences to clinical sciences.…”
mentioning
confidence: 99%